Innovation culture as a premise for engaging and memorable tourist experiences through gamification - Sonia Mileva (Tourism, 2023)
The purpose of the article is to research the impact of innovativeness and innovation culture as premises for effective gamification at destination level. The main hypothesis defended is that innovation culture and gamification can be powerful tools for tourism destination management. By creating a culture that supports innovation and implementing gamification strategies, tourism destinations can enhance their competitiveness, attract more tourists and improve the overall tourism experience. Bulgaria has been selected as the tourism destination for analysis. The methodology combines desk research with key informant surveys. The first survey is about innovativeness and innovation culture and the second is about destination gamification. Both include 18 informants, representing the travel and hospitality sectors in Bulgaria. The main findings are that innovation culture and gamification can be powerful tools for tourism destination management. The contribution is a first attempt to link innovation culture with destination management and the use of gamification as a tool for memorable tourist experiences. The article contains data and gives practical insights reflecting the Bulgarian perspective in the field.